2011
DOI: 10.1111/j.1755-9294.2011.01118.x
|View full text |Cite
|
Sign up to set email alerts
|

Gastric adenocarcinoma with choriocarcinomatous and hepatoid differentiation

Abstract: We report a patient with gastric adenocarcinoma with choriocarcinomatous and hepatoid differentiation. A 67-year-old man visited our hospital for further evaluations due to gastric adenocarcinoma. The gastric cancer was located in the prepyloric area and appeared to be a protruding mass with an infiltrative growth pattern. Initial pancreatic and postoperative hepatic and pulmonary metastases were detected radiologically. Microscopically, choriocarcinomatous and hepatoid differentiation was observed with a mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The results of disease-free survival of GAHED in the present study support the previous descriptions. Motoyama et al and Hwang et al reported a case of gastric adenocarcinoma with choriocarcinomatous and hepatoid differentiation [6,16]. They suggest that choriocarcinoma or hepatoid carcinoma may show the retrodifferentiation related to the unfavourable pathological differentiation [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of disease-free survival of GAHED in the present study support the previous descriptions. Motoyama et al and Hwang et al reported a case of gastric adenocarcinoma with choriocarcinomatous and hepatoid differentiation [6,16]. They suggest that choriocarcinoma or hepatoid carcinoma may show the retrodifferentiation related to the unfavourable pathological differentiation [16].…”
Section: Discussionmentioning
confidence: 99%
“…Motoyama et al and Hwang et al reported a case of gastric adenocarcinoma with choriocarcinomatous and hepatoid differentiation [6,16]. They suggest that choriocarcinoma or hepatoid carcinoma may show the retrodifferentiation related to the unfavourable pathological differentiation [16]. Gastric neuroendocrine carcinoma also has a propensity to behave in an aggressive clinical fashion [17].…”
Section: Discussionmentioning
confidence: 99%
“…Other germ cell tumor elements may present alongside embryonal carcinoma, yolk sac tumors, and hepatoid adenocarcinoma [ 58 59 ]. Only a few cases involving pure gastric yolk sac tumors have been documented [ 60 61 62 63 ].…”
Section: Choriocarcinomamentioning
confidence: 99%